The Anti-Leukemia Effect of Ascorbic Acid: From the Pro-Oxidant Potential to the Epigenetic Role in Acute Myeloid Leukemia - Travaglini, S.; Gurnari, C.; Antonelli, S.; Silvestrini, G.; Noguera, N. I.; Ottone, T.; Voso, M. T. (Frontiers in Cell and Developmental Biology, 2022)
Data derived from high-throughput sequencing technologies have allowed a deeper understanding of the molecular landscape of Acute Myeloid Leukemia (AML), paving the way for the development of novel therapeutic options, with a higher efficacy and a lower toxicity than conventional chemotherapy. In the antileukemia drug development scenario, ascorbic acid, a natural compound also known as Vitamin C, has emerged for its potential anti-proliferative and pro-apoptotic activities on leukemic cells. However, the role of ascorbic acid (vitamin C) in the treatment of AML has been debated for decades. Mechanistic insight into its role in many biological processes and, especially, in epigenetic regulation has provided the rationale for the use of this agent as a novel anti-leukemia therapy in AML. Acting as a co-factor for 2-oxoglutarate-dependent dioxygenases (2-OGDDs), ascorbic acid is involved in the epigenetic regulations through the control of TET (ten-eleven translocation) enzymes, epigenetic master regulators with a critical role in aberrant hematopoiesis and leukemogenesis. In line with this discovery, great interest has been emerging for the clinical testing of this drug targeting leukemia epigenome. Besides its role in epigenetics, ascorbic acid is also a pivotal regulator of many physiological processes in human, particularly in the antioxidant cellular response, being able to scavenge reactive oxygen species (ROS) to prevent DNA damage and other effects involved in cancer transformation. Thus, for this wide spectrum of biological activities, ascorbic acid possesses some pharmacologic properties attractive for anti-leukemia therapy. The present review outlines the evidence and mechanism of ascorbic acid in leukemogenesis and its therapeutic potential in AML. With the growing evidence derived from the literature on situations in which the use of ascorbate may be beneficial in vitro and in vivo, we will finally discuss how these insights could be included into the rational design of future clinical trials.